Sintesis dan Aplikasi Nanopartikel Kitosan Sebagai Adsorben Cd dan Antibakteri Koliform - Swara Yudhasasmita; Andhika Puspito Nugroho (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
Chitosan is a derivative compound of chitin which has a linear polysaccharide composed of β-(1–4)-linked d-glucosamine and N-acetyl-d-glucosamine. This compound is found in shrimp shell. In nanoparticle form, chitosan has a great antibacterial activity and adsorption ability rather than normal form. The aims of this study are to study the effect of concentration chitosan nanoparticle to adsorpt cadmium and its antibacterial effect on coliform. This research was started with synthesis of chitosan nanoparticles using acetic acid 2% and TPP 0,1 %, then the sampel was dried by spray dryer. For cadmium adsorption test was conducted by giving chitosan nanoparticle of 0.1, 0.2, 0.3, 0.4, and 0.5 g, respectively, into Cd solution with the concentration of 7 ppm and was filtered with theWhatman paper number 42 (n=3). Cadmium contents in the filtrates and pellets were analyzed by using AAS. For antibacterial test with Salmonella typhimurium andEscherichia coliwere conducted by disc diffusion method, contained of 0.1, 0.2, 0.3, 0.4, and 0.5 g, respectively, were dissolved in 50 ml of 1% acetic acid. Data were analyzed by using oneway ANOVA followed by LSD. Based on the results, the optimum adsorption of cadmium present in addition of 0.4 g/ 50mL, can reduce Cd concentration by 98,7%. For the antibacterial test, the addition of 0.4 g/50mL is the largest zone of inhibition Salmonella thypimuriumand Escherichia coli.